Methionine in a protein hydrophobic core drives tight interactions required for assembly of spider silk - Julia C. Heiby (Nature Portfolio, 2019)
Spider silk is of interest in material science research. Here the authors show that the tight binding of a spider silk protein domain relies on the amino acid methionine, which is abundant in the domain core where it facilitates dynamic shape adaption of the binding interface.